Encapsulating biopolymeric microparticles within floating capsules for oral delivery of drugs - Low, Celine Yan Jing (Nanyang Technological University, 2022)
Solid lipid microparticles (LMP) are alternatives to polymeric nanoparticles for the encapsulation of hydrophobic components that have poor bioavailability. However, the usual method of fabrication of solid LMP through high pressure homogenization had limitations that caused low encapsulation efficiency and potential damage to sensitive molecules. Hence the electrospray technique was investigated as an alternative. In this study, for the fabrication of solid LMP, the electrospray method was explored by varying different parameters such as flow rate and voltage. Scanning Electron Microscopy (SEM) was used to characterize the microparticles. Following the optimization of parameters, curcumin was loaded into the microparticle. Release studies of the curcumin loaded particles in simulated gastrointestinal fluids showed that the encapsulation was able to retard the release of curcumin in simulated gastric fluid (SGF) and release it in the simulated intestinal fluid (SIF). In order to prolong the release of curcumin, the curcumin loaded LMP were further encapsulated into floating particles that can act as a reservoir for LMP. Based on SEM images it was observed that the LMP were mainly localized on the surface of the floating microparticles. Further in vitro release studies on the floating particles need to be conducted to understand the behavior of LMP in the floating particles.